Hak Cipta dalam Perspektif Hukum Islam - Supeno Supeno (Wajah Hukum, 2018)
Intellectual property (HKI) is one of the rights that have been getting protection by law in Indonesia, there are some regulations that govern on rights that are included in the scope of intellectual kekayan as copyrights, patent rights, trademark rights, trade secret rights and so on. To know more deeply is how copyright in the perspective of Islamic law because Indonesia as the country's largest Islamic religion will greatly affect the understanding and awareness of the importance of the protection of the population of Indonesia against intellectual property.